2022
DOI: 10.3390/separations9090234
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Total Phenolic and Flavonoid Content and LC–MS Profiling of Leaves Extracts of Alstonia angustiloba

Abstract: Plants have a wide range of active compounds crucial in treating various diseases. Most people consume plants and herbals as an alternative medicine to improve their health and abilities. A. angustiloba extract showed antinematodal activity against Bursaphelenchus xylophilus, antitrypanosomal action against Trypanosoma brucei and anti-plasmodial activity against the chloroquine-resistant Plasmodium falciparum K1 strain. Moreover, it has demonstrated growth inhibitory properties towards several human cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…The TFC of K. fedtschenkoi methanol extract was determined as published [ 78 ]. Shortly, 100 μL of methanol extract (1 mg/mL) mixed with 100 μL of 2% aluminum chloride (AlCl 3 ) was incubated for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The TFC of K. fedtschenkoi methanol extract was determined as published [ 78 ]. Shortly, 100 μL of methanol extract (1 mg/mL) mixed with 100 μL of 2% aluminum chloride (AlCl 3 ) was incubated for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the varying polarity and chemical properties of these compounds, which has an impact on their solubility in the solvent used, the nature of the extraction solvent has a significant effect on the extraction yields. [14] The present study revealed a difference in total phenolic content (TPC) and total flavonoid content (TFC) among different solvent extracts of S. tundjeliensis (Table 1). TPC was in the range 22.86 ± 1.04 to 81.86 ± 0.86 mg GAE/g.…”
Section: Phytochemical Profilementioning
confidence: 61%
“…Because of the varying polarity and chemical properties of these compounds, which has an impact on their solubility in the solvent used, the nature of the extraction solvent has a significant effect on the extraction yields. [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC-MS is a powerful tool for the fast determination of bioactive components in herbal medicines. It has been widely used for the rapid assay of challenging-to-separate components in many herbal medicines [20][21][22][23]. HPLC-MS technology combines the separation abilities of HPLC with the detection abilities of MS, offering the advantages of high resolution, high selectivity, and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%